LITERASI KRITIS DALAM PEMBELAJARAN UNTUK MEMBENTUK KARAKTER DAN REVITALISASI NILAI PANCASILA - Pawit Abimaba; Pargito Pargito; Irawan Suntoro (Jurnal Studi Sosial / Journal of Social Studies, 2013)
The goal of this research is to know using learning with Critical Literacy Perspective model that can form students’ character and can revitalize Pancasila value. This was a classroom action research, that was a study toward classroom learning action which was being upgraded continuously to reach the goal, by using Kemmis and Taggard cycles that contained the plan of observation and  reflection action. The instrument of data collecting used observation toward learning process. The result form of character in Cycle I with score 70, 714, second Cycle reach ed an increase 85,476 and increased became with score 90, 475 in Cycle III; and the revitalization of Pancasila value in cycle I with score 72, 143, in second cycle increased to be 85,714 and in Cycle III increased with score 91,190.Based on the result of this research, it can be concluded that the implementation of learning model which has critical literacy perspective can form students’ character and can  revitalize Pancasila value.Keywords: PTK,  critical literacy, character, revitalization of pancasila value.